Makna Social Drinking pada Film Korea Selatan di Netflix Tahun 2024: Analisis Semiotika Charles Sanders Pierce - Moch. Nauval Al Gifari; Rizca Haqqu (STIKes Ibnu Sina Ajibarang, 2026)
This study aims to analyze the cultural meaning of social drinking displayed in South Korean films on Netflix in 2024 through the perspective of Charles Sanders Peirce's semiotic theory. Social drinking, as a cultural phenomenon, is not only a social habit in South Korea but is also often used as a narrative element in films to convey cultural values, social dynamics, and interpersonal relationships. Qualitative research methods with a semiotic analysis approach are used to explore the meaning displayed on the representamen, object, and interpretant sides of social drinking in the films Badland Hunters, Officer Black Belt, Mission: Cross, Wonderland, and My Name is Loh Kiwan. The results of the study show that social drinking represents the culture of togetherness of South Korean society that is woven into various contexts, such as work relationships, family, and friendships. In terms of representamen, visual signs in the form of symbols of drinking culture such as soju, banquet tables, and the movement of pouring drinks to each other create a strong picture of togetherness. From the object side, social drinking becomes a medium to highlight solidarity and release social pressure, especially in a hierarchical and competitive work culture. The resulting interpretation shows a dualism of meaning: on the one hand, it strengthens harmony and the value of togetherness, while on the other hand it displays the dark side of this culture, such as excess consumption and its influence on social pressure. This study provides new insights into the role of South Korean films as a medium for conveying global cultural messages, which are able to influence local cultural interpretations outside their country of origin. In addition, this study is expected to enrich the literature on semiotics in visual communication studies with a focus on drinking culture as an element of representation.